Project management in the regulatory pharmaceutical environment - Ragnhildur Nielsen 1975- (2012)
By submitting a central procedure with the European Medicines Agency the marketing authorisation holder receives a marketing authorisation for the whole European Union as well as the EFTA states (Iceland, Liechtenstein and Norway). In this paper it is proposed that certain aspects of the agile method, DSDM are incorporated within the project management handling the procedure both before and after marketing authorisation.